Bolus rheology of texture‐modified food: Effect of degree of modification. Issue 5 (4th May 2021) - Stading, Mats
Abstract: Swallowing disorders, or dysphagia, require an intake of texture‐modified foods progressively softer, smoother, and moister depending on the severity of the disorder. Bolus rheology was determined for five healthy subjects for a set of such solid foods regularly given to dysphagia patients. The softest class was gel food, then a smooth timbale which both were compared to the corresponding regular, un‐modified food. The foods investigated were bread, cheese, tomato, and the combination as a sandwich, all for the respective texture class: gel, timbale, and regular food. The subjects chewed until ready to swallow and the expectorated bolus was immediately measured for complex shear modulus and viscosity, and moisture and saliva content were determined. Rheology show that texture‐modification influenced bolus rheology with decreased viscosity and modulus for increased degree of modification. Also saliva content as well as chews‐to‐swallow decreased with degree of modification. Overall, the bolus saliva content was lower for the combination (sandwich) than for the individual components. Saliva content was fairly constant irrespective of food moisture content. The phase angle for all boluses was also relatively constant, indicating a similar bolus structure. All boluses of the texture‐modified foods showed high extensional viscosity, which is important for bolus cohesiveness. Bolus rheology rather than food texture determines if a food is safe to swallow and the results show that the intended texture‐modification is reflected in the flow properties of the respective boluses. Abstract : Texture modification for dysphagia management is in general reflected by bolus rheology and required saliva addition and amount of chewing decreases with texture modification level. Bolus viscosity and modulus also decrease with texture modification. A combination of food components is better for easy swallowing than the components alone.